Protective Effect of Catharanthus roseus Extract on Cadmium-Induced Toxicity in Albino Rats: A Putative Mechanism of Detoxification - Mohammad Hashim; Hussain Arif; Baby Tabassum; Amin Arif; Ahmed A. Rehman; Shahnawaz Rehman; Rehnuma Khanam; Bushra Khan; Arif Hussain; Jameel Barnawi; Faris J. Tayeb; Naseh Algehainy; et al. (Metabolites, 2022)
Globally, people are highly affected by Cadmium (Cd), the most hazardous heavy metal. It has been implicated in various pathogeneses. Oxidative stress may be one the main reasons for Cd-induced disorders in the body. This article investigates the protective ability of Catharanthus roseus (CR) extract on oxidative stress in the kidney and liver of rats exposed to Cd. After 21 days, a significant increase in MDA concentration (6.81 ± 0.05), (6.64 ± 0.03) was observed in Cd-treated groups compared to the control (5.54 ± 0.02), (5.39 ± 0.04) for the kidney and liver, respectively, while significant changes were observed in the haematological parameters. Antioxidant enzymes, GPx, CAT, and SOD showed a significant decrease in their activity. We established that increasing the concentration of Cd in the presence of H2O2 was able to cause stand scission in pBR322 plasmid DNA, which may be due to the mediation of ROS generated in the process. The antioxidant ability of CR extract was tested in DPPH and H2O2 scavenging assay, depicted by the increase in the percentage inhibition. Upon treatment of CR extract to rats, MDA concentration was decreased for the kidney and liver compared to the Cd-treated groups. This was again confirmed by comet assay of both tissues, where the degree of cellular DNA breakage caused by Cd toxicity decreased significantly upon treatment with CR extract. Overall, the results suggest that Cd plays a major role as an effector metal ion, causing a decrease in the concentration and activity of AO enzymes and enhanced lipid peroxidation. ROS production resulted in oxidative DNA damage within the cell, whereas CR extract showed potential antioxidant activity against ROS-mediated DNA damage induced by Cd poisoning.